8-Hydroxy-5-(hydroxymethyl)quinolin-1-ium chloride - Fathi, Majda (International Union of Crystallography, 2012)
The title compound, C(10)H(10)NO(2) (+)·Cl(−), contains a quinoline ring system which is essentially planar, with the largest deviation from the mean plane being 0.017 (1) Å. In the crystal, the ion pairs and their inversion-symmetry-related partners are linked by N—H⋯Cl and O—H⋯Cl hydrogen bonds to form tetramers which are further connected through O—H⋯O hydrogen bonds, building infinite one-dimensional chains parallel to the [010] direction.